Influence of Phosphate on Network Connectivity and Glass Transition in Highly Polymerized Aluminosilicate Glasses - Grammes, Thilo; de Ligny, Dominique; Scheffler, Franziska; Nizamutdinova, Alina; Wu''Llen, Leo Van; Kamitsos, Efstratios I.; Massera, Jonathan; Brauer, Delia S. (Journal of Physical Chemistry B, 2022)
Melt-derived metaluminous (Al/Na = 1) aluminosilicate glasses in the system SiO2-Al2O3-Na2O-P2O5were prepared with P2O5and SiO2contents varying from 0 to 7.5 and 50 to 70 mol %, respectively. The glass structure was investigated by X-ray absorption near edge structure, far- and medium-infrared, and polarized Raman spectroscopic techniques. The results indicate the incorporation of phosphate into the aluminosilicate network not only as partially depolymerized groups but also as fully polymerized groups charge-balanced by aluminate units in Al-O-P bonds. A new analysis method based on polarized Raman spectra in the bending frequency range indicates a preference of phosphate to reorganize the smallest ring structures. Changes in the glass transition temperature with the increase in phosphate content were found to be consistent with the depolymerization of the network structure shown by spectroscopy. By contrast, increasing the silica content by substituting SiO4for AlO4tetrahedra, while keeping the phosphate content constant, was found to have a negligible effect on network polymerization. Still, the glass transition temperature decreased and correlated with a far-infrared sodium band shift to higher frequency. This was interpreted as local changes in bond strength caused by complex interactions between the different network formers and sodium ions.
CRIS-Team Scopus Importer:2022-12-23